Symmetric sum and also geometric sum

Algebra Level 4

Determine the number of distinct positive triplets ( x , y , z ) (x,y,z) such that x + y + z , x 2 + y 2 + z 2 , x 3 + y 3 + z 3 x+y+z , x^2 + y^2+ z^2 ,x^3 + y^3 + z^3 are distinct numbers that follows a geometric progression in that order.

0 2 1 3

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Hung Woei Neoh
Jun 21, 2017

Since this is a geometric progression, we can write an equation based on the common ratio:

x 2 + y 2 + z 2 x + y + z = x 3 + y 3 + z 3 x 2 + y 2 + z 2 ( x 2 + y 2 + z 2 ) 2 = ( x + y + z ) ( x 3 + y 3 + z 3 ) x 4 + y 4 + z 4 + 2 x 2 y 2 + 2 x 2 z 2 + 2 y 2 z 2 = x 4 + y 4 + z 4 + x 3 y + x y 3 + x 3 z + x z 3 + y 3 z + y z 3 x 3 y 2 x 2 y 2 + x y 3 + x 3 z 2 x 2 z 2 + x z 3 + y 3 z 2 y 2 z 2 + y z 3 = 0 x y ( x 2 2 x y + y 2 ) + x z ( x 2 2 x z + z 2 ) + y z ( y 2 2 y z + z 2 ) = 0 x y ( x y ) 2 + x z ( x z ) 2 + y z ( y z ) 2 = 0 \dfrac{x^2+y^2+z^2}{x+y+z} = \dfrac{x^3+y^3+z^3}{x^2+y^2+z^2}\\ (x^2+y^2+z^2)^2 = (x+y+z)(x^3+y^3+z^3)\\ {\color{#D61F06}x^4+y^4+z^4}{\color{#20A900}\,+\,2x^2y^2}{\color{#EC7300}\,+\,2x^2z^2}{\color{#3D99F6}\,+\,2y^2z^2 }= {\color{#D61F06}x^4+y^4+z^4}{\color{#20A900}\,+\,x^3y+xy^3}{\color{#EC7300}\,+\,x^3z+xz^3}{\color{#3D99F6}\,+\,y^3z+yz^3}\\ {\color{#20A900}x^3y-2x^2y^2+xy^3}{\color{#EC7300}\,+\,x^3z-2x^2z^2+xz^3}{\color{#3D99F6}\,+\,y^3z-2y^2z^2+yz^3} = 0\\ {\color{#20A900}xy(x^2-2xy+y^2)}{\color{#EC7300}\,+\,xz(x^2-2xz+z^2)}{\color{#3D99F6}\,+\,yz(y^2-2yz+z^2)} = 0\\ {\color{#20A900}xy(x-y)^2}{\color{#EC7300}\,+\,xz(x-z)^2}{\color{#3D99F6}\,+\,yz(y-z)^2} = 0

Note that since x y z x \neq y \neq z , we know that x y 0 \color{#20A900}x-y \neq 0 , x z 0 \color{#EC7300}x-z \neq 0 and y z 0 \color{#3D99F6}y-z \neq 0

None of the numbers x , y x,y and z z are 0 0 . Suppose x = 0 x= 0 . Then, y z ( y z ) 2 = 0 \color{#3D99F6}yz(y-z)^2 = 0 , which implies that y = x = 0 y=x=0 or z = x = 0 z=x=0 , since y z 0 \color{#3D99F6}y-z \neq 0 . This contradicts the fact that x y z x \neq y \neq z . The same argument holds if y = 0 y=0 or z = 0 z=0

Then, suppose that x , y , z > 0 x,y,z > 0 . We know that x y > 0 , ( x y ) 2 > 0 , x z > 0 , ( x z ) 2 > 0 , y z > 0 , ( y z ) 2 > 0 {\color{#20A900}xy > 0, (x-y)^2 > 0}\,,\, {\color{#EC7300}xz > 0, (x-z)^2 > 0}\,,\, {\color{#3D99F6}yz > 0, (y-z)^2 > 0} . This implies that the expression x y ( x y ) 2 + x z ( x z ) 2 + y z ( y z ) 2 > 0 {\color{#20A900}xy(x-y)^2}{\color{#EC7300}\,+\,xz(x-z)^2}{\color{#3D99F6}\,+\,yz(y-z)^2} >0 .

Hence, 0 \boxed{0} distinct positive triplets ( x , y , z ) (x,y,z) satisfy the given requirements

yes, it's essentially show that "sum of positive numbers = 0 ==> contradiction." Nicely done! +1 for colors!

Bonus: Can we also solve this problem if we replace the word "geometric" with "arithmetic" (or "harmonic")?

Pi Han Goh - 3 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...